SOCIOCULTURAL DYNAMICS AND ECONOMIC DEVELOPMENT (TO THE 130TH ANNIVERSARY OF P. A. SOROKIN) - D. K. Stozhko (Дискурс, 2018)
The views of P. A. Sorokin in the context of sociocultural determination of the socio-economic development of society are analyzed. The author proves the special role of the ideas under consideration in the development of economic thought of the twentieth century, their succession to the "Russian religious renaissance" and Russian economic science, and also describes their fundamental differences from modern economic liberalism, which they definitely respond to. Despite some problematic and controversial ideas of sociocultural dynamics concept of P. A. Sorokin, the conclusions about the influence of culture on economic processes are confirmed by modern economic practices.